Isotopic study of Raman active phonon modes in β-Ga2O3. Issue 7 (21st January 2021) - Janzen, Benjamin M.; Mazzolini, Piero; Gillen, Roland; Falkenstein, Andreas; Martin, Manfred; Tornatzky, Hans; Maultzsch, Janina; Bierwagen, Oliver; Wagner, Markus R.
Abstract : The Raman-active phonon modes of β-Ga2 O3 in two O isotope compositions are studied by theory and experiment. Raman modes dominated by different, inequivalent O lattice sites were identified and can be used for the investigation of point defects. Abstract : Holding promising applications in power electronics, the ultra-wide band gap material gallium oxide has emerged as a vital alternative to materials like GaN and SiC. The detailed study of phonon modes in β-Ga2 O3 provides insights into fundamental material properties such as crystal structure and orientation and can contribute to the identification of dopants and point defects. We investigate the Raman active phonon modes of β-Ga2 O3 in two different oxygen isotope compositions ( 16 O, 18 O) by experiment and theory: By carrying out polarized micro-Raman spectroscopy measurements on the (010) and (2̄01) planes, we determine the frequencies of all 15 Raman active phonons for both isotopologues. The measured frequencies are compared with the results of density functional perturbation theory (DFPT) calculations. In both cases, we observe a shift of Raman frequencies towards lower energies upon substitution of 16 O with 18 O. By quantifying the relative frequency shifts of the individual Raman modes, we identify the atomistic origin of all modes (Ga–Ga, Ga–O or O–O) and present the first experimental confirmation of the theoretically calculated energy contributions of O lattice sites to Raman modes. The DFPT results enable the identification of Raman modes that are dominated by the different, inequivalent O- or Ga-atoms of the unit cell. We find that oxygen substitution on the OIII site leads to an elevated relative mode frequency shift compared to OI and OII sites. This study presents a blueprint for the future identification of different point defects in Ga2 O3 by Raman spectroscopy.